2002
DOI: 10.1348/135910702169411
|View full text |Cite
|
Sign up to set email alerts
|

Influence of attention focus and trait anxiety on tolerance of acute pain

Abstract: The results are consistent with the notion that anxiety fosters attentiveness to possible environmental threats, and might have implications for the clinical management of acute pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
72
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 0 publications
15
72
3
Order By: Relevance
“…Results showed that, overall, participants in both distraction groups reported significantly less pain intensity compared to the control group. These results are consistent with other studies that also found similar beneficial effects of distraction on pain [25,26,37,38,42,51]. However, our study has further value over previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Results showed that, overall, participants in both distraction groups reported significantly less pain intensity compared to the control group. These results are consistent with other studies that also found similar beneficial effects of distraction on pain [25,26,37,38,42,51]. However, our study has further value over previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Anxiety is associated with subjective feelings of apprehension about impending or anticipated harm 34 , autonomic arousal (increased heart rate) and avoidance behaviour. Both state and trait anxiety can result in increased pain sensitivity, increased report of pain intensity and reduced pain tolerance [34][35][36][37][38][39] . Negative expectations of pain, or pain worsening, induce anticipatory anxiety about the impending pain, thus triggering the activation of the neuropeptide cholecystokinin which can facilitate pain transmission 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Dalgleish & Power, 2004), or the consideration of fear and anxiety as distinct emotions (e.g. James & Hardardottir, 2002). The space limitations prevented such analyses, that could however be pursued in further studies.…”
Section: Discussionmentioning
confidence: 99%